Disentangling the Role of the MEC and LEC in the Processing of Spatial and Non-Spatial Information: Contribution of Lesion Studies - Save, Etienne; Sargolini, Francesca (Frontiers in Systems Neuroscience, 2017)
It is now widely accepted that the entorhinal cortex (EC) plays a pivotal role in the processing of spatial information and episodic memory. The EC is segregated into two sub-regions, the medial EC (MEC) and the lateral EC (LEC) but a comprehensive understanding of their roles across multiple behavioral contexts remains unclear. Considering that it is still useful to investigate the impact of lesions of EC on behavior, we review the contribution of lesion approach to our knowledge of EC functions. We show that the MEC and LEC play different roles in the processing of spatial and non-spatial information. The MEC is necessary to the use of distal but not proximal landmarks during navigation and is crucial for path integration, in particular integration of linear movements. Consistent with predominant hypothesis, the LEC is important for combining the spatial and non-spatial aspects of the environment. However, object exploration studies suggest that the functional segregation between the MEC and the LEC is not as clearly delineated and is dependent on environmental and behavioral factors. Manipulation of environmental complexity and therefore of cognitive demand shows that the MEC and the LEC are not strictly necessary to the processing of spatial and non-spatial information. In addition we suggest that the involvement of these sub-regions can depend on the kind of behavior, i.e., navigation or exploration, exhibited by the animals. Thus, the MEC and the LEC work in a flexible manner to integrate the “what” and “where” information in episodic memory upstream the hippocampus.